2018
DOI: 10.2147/opth.s163859
|View full text |Cite
|
Sign up to set email alerts
|

Anti-VEGF treatment of macular edema associated with retinal vein occlusion: patterns of use and effectiveness in clinical practice (ECHO study report 2)

Abstract: PurposeTo evaluate the efficacy, safety, and injection frequency of vascular endothelial growth factor (VEGF) antagonists in the treatment of macular edema secondary to retinal vein occlusion (RVO) in clinical practice.Patients and methodsA multicenter retrospective study of the medical records of 165 patients (95 branch RVO, 70 central RVO) treated with at least three anti-VEGF injections in the study eye was conducted. Available data collected for at least 6 months after the first injection included Snellen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 33 publications
(50 reference statements)
1
34
1
Order By: Relevance
“…That is why the present ophthalmological standard recommends intravitreal antiVEGF or steroids in the treatment of macular edema secondary to RVO [88,89]. However, the functional results of such a treatment are not always satisfactory.…”
Section: Smplt In Me Secondary To Rvomentioning
confidence: 99%
“…That is why the present ophthalmological standard recommends intravitreal antiVEGF or steroids in the treatment of macular edema secondary to RVO [88,89]. However, the functional results of such a treatment are not always satisfactory.…”
Section: Smplt In Me Secondary To Rvomentioning
confidence: 99%
“…This, in addition to the issue of patient compliance, results in a problem of inadequate treatment. It has been shown that patients generally received less injections than that given in clinical trials for n-AMD [30,31], DMO and RVOs [31][32][33]. This limits the effectiveness of anti-VEGF therapy in retinal vascular diseases [30][31][32][33][34][35][36].…”
Section: Limitations Of Anti-vegf Agents In the Treatment Of Retinal mentioning
confidence: 99%
“…Although baseline BCVA in BRVO group is worse than other studies, the final BCVA outcome in BRVO ( 0.25 + 0.11 logMAR equivalent to Snellen 20/40) is comparable to other literatures, even with PRN regime and low frequency of injection. [16][17][18][19] This is probably because BRVO had more benign nature of the disease and also younger age compared to CRVO.…”
Section: Number Of Injections During Follow-upmentioning
confidence: 99%